CUSTOMER-COMMUNITY EFFICIENCY OF ISLAMIC BANKS COMPARED TO NON-ISLAMIC BANKS IN INDONESIA FROM 2010 TO 2016 - Rejeki, Tari Sri; Faturohman, Taufik (Journal of Business and Management, 2017)
Abstract. The Islamic banks has the good reputation in the country with the Muslim minority. Based on the analysis of vision and mission statement of banks in Indonesia. This study to prove the statement of Islamic banks and also to see the movement of customer-community efficiency of Islamic and non-Islamic banks from 2010-2016. The study focus on the growth of market share calculated from total deposits, if the growth of total deposits increases then market share will also increase. The Variable Return to Scale DEA is used to measure the customer and community efficiency of banks. Then the Mann-Whitney test is used to determine whether the customer-community efficiency Islamic banks differ from the non-Islamic banks in Indonesia. Analysis the movement of customer-community efficiency from Islamic and non-Islamic banks is based on the single multiyear DEA result, and the Spearman’s correlation used to analyze the correlation between banks efficiency and market share. The result of this research is, based on the DEA annual frontier results show that only in 2010 the efficiency of Islamic banks and non-Islamic banks is not significant difference. The Single multiyear results show that the customer-community efficiency of Islamic banks in 2010 to 2013 actually ups and downs. But in 2014-2016 the Islamic banks show a positive trend and begin to pursue non-Islamic bank but the efficiency is not as big as the non-Islamic bank's efficiency. Similar to non-Islamic banks, Islamic banks have the significant correlation between the customer-community efficiency and the market share, and also the correlation is strong. It means that good services of banks affect the market share. The result means that if the customer-community efficiency increases then the market share of banks also increases. Many factors can affect the market share of banks such as economic conditions, IT used by banks to serve the customers and the community, and accessibility.Keywords: Customer-Community efficiency, Islamic bank, Non-Islamic bank.